(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To describe the therapeutic itinerary of people with an ostomy in search of specialized care. Method: exploratory, descriptive study with a qualitative approach, with ten people with ostomy treated at the Ostomy Care Service (Serviço de Atenção à Saúde da Pessoa Ostomizada), from August to November 2017. Reconstitution took place through semi-structured interviews, registration in a field diary and consultation with records of specialized health services, and processed by the software Interface de R pour les Analyses Multidimensionnelles de Texte et de Questionnaires. Results: the therapeutic itinerary begins with the discovery of signs and symptoms, when there is access to the nearest health services and later in search of specialized services. Marked by formal connections and supported by interrelated subsystems. The trajectories of search, production, health transport and health care management undertaken by individuals, families and informal groups express different paths and movements in the phase that precedes specialized care. Conclusion: the knowledge apprehended by the speeches enables the identification of basic needs presented by this clientele, facilities and barriers encountered in the course undertaken to obtain an adequate therapeutic plan.